Narrative and the self - Kerby, Anthony Paul, 1953- (Indiana University Press, 1991)
Examining the constitutive role of language and narration in key areas of human experience, Narrative and the Self articulates a view of the self as the implied subject of narrative utterances. Anthony Paul Kerby draws on the diverse insights of recent work in philosophy, literary theory, and psychology to synthesize a coherent and provocative view of narrative identity and selfhood. Invoking the writings of Benveniste, Ricoeur, Merleau-Ponty, Lacan, Taylor, and other theorists, he argues that language and narration play a central role in key aspects of human experience such as emotion, values, recollection, and sense of history. Fundamental to Kerby's exposition is a defense of the quasi-narrative nature of our every- day experience. Kerby delineates a convincing narrative model of the self and offers a valuable overview of contemporary philosophical issues surrounding the place and role of narrative in human experience.
Keywords: Discourse analysis, Narrative.; Self (Philosophy); Language and languages -- Philosophy.; Discours narratif.; Moi (Philosophie); Langage et langues -- Philosophie.; REFERENCE.; LANGUAGE ARTS & DISCIPLINES -- Vocabulary.; Discourse analysis, Narrative; Language and languages -- Philosophy; Philology & Linguistics.; Languages & Literatures.